B135 Peripheral nerve catheter postoperative care. (11th August 2022) - Mustafa, Y; Ndu, K; Akhtar, N; Shalaby, A; Dunn, A; Pascu, D; Smith, B
Abstract : Background and Aims: The benefits of peripheral nerve catheters are well documented [1]. They include superior analgesia, patient satisfaction and functional recovery, as well as reduction of joint inflammation and chronic pain development. Although the acute pain service has been suggested as being able to manage catheters on the ward [2], we aimed to investigate their postoperative management at our hospital. Methods: After catheter insertion in March 2022, the anaesthetist completed a short online survey (http://blox.tube). The surgical procedure, site and postoperative care instructions were recorded. We also surveyed the ward staff to assess their confidence in managing nerve catheters and methods to improve this. Results: We received 27 responses. 48.2% catheters were inserted for total knee replacements, 25.9% for lower limb amputations and 22.2% for shoulder procedures. 62.1% were femoral, 13.8% were sciatic and 20.7% were interscalene nerve catheters. In 81.5% of cases, there was only a prescription. In 11.1% there was an accompanying note scheduling catheter removal for the following day at 6am and in 7.4% there was an instruction on the anaesthetic chart to remove in 24–48 hours. 18 ward nurses, doctors and physiotherapists were surveyed. They had a median confidence of 55% [IQR 22.5–80%] in managing nerve catheters and 88.9% felt a care protocol would be useful. Conclusions: There is widespread inconsistency in managing peripheral nerve catheters on the wards with a lack of communication between the anaesthetic and ward teams in most cases. A peripheral nerve catheter care protocol and record with clear instructions regarding management and escalation pathways is required.